THE DIALOGICAL CHARACTER OF QUALITATIVE RESEARCH - Simone Antoniaci Tuzzo (2023)
About methodology in the context of Social Sciences, the literature has focused on two main vectors: the differentiation between qualitative and quantitative methodologies and the possibilities of complementarity between both. This theoretical-methodological essay does not intend to deepen the characteristics of the methodologies, nor to advocate any type of incompatibility between them, but it aims to reflect on the extent to which qualitative methodologies are exclusively qualitative and, above all, quantitative ones are exclusively quantitative. For this, it intends to reflect on the following epistemological questions: What is the importance of qualitative analysis in the context of research, especially empirical ones, and in what way can and should they assume a dialogical character with quantitative research actions? What is qualitative within quantitative research? Based on studies of the triangulation process of qualitative research previously developed by the authors, the theoretical-methodological reflection that is now presented in this article, intends to respond to the concern about the intertwined relationship between qualitative and quantitative research. Although in quantitative research numerical results are the main support base, especially in relation to social phenomena, the importance of understanding the data in a contextualized way about sociocultural experiences and the processes of construction of the social fabric is evident, which implies for on the one hand, a dialogue between a subject (capable of reflection and interpretation) and an object of study (reflected in the results). On the other hand, between qualitative and quantitative methodologies. The result reflects the non-existence of rigid limits that prevent an imbrication between the methods. However, in addition to the classic triangulation, it is considered that in qualitative research there is also data quantification, but also in quantitative research, different steps are carried out in the light of qualitative processes. In conclusion, it is necessary to think that the dialogicity of the research occurs in all stages of its development.